2021
DOI: 10.1186/s43058-020-00102-9
|View full text |Cite
|
Sign up to set email alerts
|

Applying human-centered design to maximize acceptability, feasibility, and usability of mobile technology supervision in Kenya: a mixed methods pilot study protocol

Abstract: Background Although research continues to support task-shifting as an effective model of delivering evidence-based practices (EBPs), little scholarship has focused how to scale up and sustain task-shifting in low- and middle-income countries, including how to sustainably supervise lay counselors. Ongoing supervision is critical to ensure EBPs are delivered with fidelity; however, the resources and expertise required to provide ongoing supervision may limit the potential to scale up and sustain … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…This study used an iterative and mixed methods approach, with qualitative interviews and a HCD workshop informing the development of the implementation guidelines and outreach strategy, which was subsequently tested in a randomized pilot trial. Full trial procedures are described elsewhere (Triplett et al, 2021). The trial was situated within a larger trial that examined the effectiveness and implementation of a locally adapted version of TF-CBT (Cohen et al, 2006) in Bungoma, Kenya (Building and Sustaining Interventions for Children [BASIC]; see Dorsey et al, 2020a for parent trial protocol).…”
Section: Methodsmentioning
confidence: 99%
“…This study used an iterative and mixed methods approach, with qualitative interviews and a HCD workshop informing the development of the implementation guidelines and outreach strategy, which was subsequently tested in a randomized pilot trial. Full trial procedures are described elsewhere (Triplett et al, 2021). The trial was situated within a larger trial that examined the effectiveness and implementation of a locally adapted version of TF-CBT (Cohen et al, 2006) in Bungoma, Kenya (Building and Sustaining Interventions for Children [BASIC]; see Dorsey et al, 2020a for parent trial protocol).…”
Section: Methodsmentioning
confidence: 99%
“…Increasingly academic publications are employing Agile methods. For example, a Kenyan mixed-method study combined qualitative interviews with human centred design workshops to engage users in designing and tailoring an intervention to fit the low-resource context ( 47 ).…”
Section: Limitationsmentioning
confidence: 99%
“…Methodologies such as human-centered design and community-based participatory research, which emphasize engagement with stakeholders to develop solutions to problems identified within the community, are recommended approaches to enhance the acceptability and feasibility of interventions to enhance adoption and eventually sustainment (Kia-Keating et al, 2017;Triplett et al, 2021). For example, LHWs in Chicago schools were trained to deliver an evidence-based parenting program, but engagement remained low, as very few parents attended the traditional parenting groups.…”
Section: Adoption: What Leads Lhws To Adopt Ebps?mentioning
confidence: 99%